2019
DOI: 10.1039/c9nj02661d
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cr(vi) from aqueous solution using magnetic modified biochar derived from raw corncob

Abstract: Magnetic modified-corncob biochar with an impregnation ratio of iron at 20% (w/w) was used for removal of Cr(vi) from aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 41 publications
1
25
0
1
Order By: Relevance
“…For WSC, KOH modified had the highest saturation adsorption capacity because KOH had a high hole expansion ability. 45 , 46 During the pretreatment process, KOH removed a large amount of ash inside the pores and had an ablation effect that made the micropores thinner or burned through, which increased the pore size to facilitate the adsorption. The saturation adsorption capacity after H 3 PO 4 treatment was the lowest, which may have been due to the higher lignin content in the walnut shell, which facilitated the formation of biochar carbonization.…”
Section: Resultsmentioning
confidence: 99%
“…For WSC, KOH modified had the highest saturation adsorption capacity because KOH had a high hole expansion ability. 45 , 46 During the pretreatment process, KOH removed a large amount of ash inside the pores and had an ablation effect that made the micropores thinner or burned through, which increased the pore size to facilitate the adsorption. The saturation adsorption capacity after H 3 PO 4 treatment was the lowest, which may have been due to the higher lignin content in the walnut shell, which facilitated the formation of biochar carbonization.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed batch experiments were conducted to evaluate the effects of various parameters 16,19,20 (pH, initial phosphate concentration, contact time, and adsorbent dose) on the adsorption capacity of AgNPs-TAC for phosphate. Briefly, predetermined amounts of AgNPs-TAC were added into the 50 mL Erlenmeyer flasks containing 25 mL of K 2 HPO 4 solution.…”
Section: Batch Adsorption Experiments Initially An Adsorption Expermentioning
confidence: 99%
“…On the basis of the analysis and discussion regarding the BET surface area and pore volume data of the biochars, it is clearly that the contribution of the pore-lling mechanism in RR24 adsorption onto the biochars was negligible. The BET surface area and pore volume of the biochars, which were applied in this study, were similar to some other biochars such as cassava rind carbon, 22 iron-modied biochar from corncob, 39 and eucalyptus bark bio-char. 12…”
Section: Physical Properties Of the Adsorbentsmentioning
confidence: 53%
“…This trend was similar to that of the previously reported studies. [37][38][39] For instance, Nguyen et al (2019) 38 indicated that the Cr(VI) adsorption capacity of Ag nanoparticle-modied activated carbon increased with the Ag nanoparticle loading ratio and reached a plateau at a loading ratio of 2 wt%. Trinh et al (2020) 37 reported that the optimal Ag nanoparticle loading for the adsorption of P was 3 wt%.…”
Section: Effect Of Zno Nanoparticle Loading Ratio On Rr24 Adsorption mentioning
confidence: 99%